2011
DOI: 10.1007/s00436-011-2486-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic study of Setaria cervi based on mitochondrial cox1 gene sequences

Abstract: The objective of the present study was to examine the phylogenetic position of Setaria cervi based on sequences of mitochondrial cytochrome c oxidase subunit 1 (cox1) gene. A fragment of the cox1 gene from two morphologically identified S. cervi collected from red deer (Cervus elaphus) from Italy were amplified, sequenced, and compared with corresponding sequences of other filarioid nematode species. Phylogenetic studies using Bayesian analysis revealed S. cervi as monophyletic with other Setaria species, conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Despite the low bootstrap values, the general topology of the Setaria spp. resembles a previously published tree by Alasaad et al. (2012) .…”
Section: Resultssupporting
confidence: 69%
“…Despite the low bootstrap values, the general topology of the Setaria spp. resembles a previously published tree by Alasaad et al. (2012) .…”
Section: Resultssupporting
confidence: 69%
“…The phylogenetic relationships of filarioid parasites have been assessed on morphological characters [ 6 , 7 ]. Nevertheless, molecular analyses are needed to confirm their morphological descriptions or taxonomic position and classification, and to improve our understanding of the species epidemiology [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, over history, many controversies about these two and other species have arisen, where authors described old species as new ones (reviewed in Nikander et al, 2007). On the molecular level, the difference between these two species is more pronounced and was shown in the phylogenetic study of Setaria cervi in Italy, which revealed that S. labiatopapillosa belong to one clade together with S. cervi and S. digitata , which is well separated from the one containing S. tundra and S. equina (Alasaad et al, 2012). In Croatia, from the first finding and over the past decades, the only previous detailed description available is from S. labiatopapillosa in cattle (Mikačić, 1941), where the author, besides the presence of lateral lips, clearly describes the thorn structures on the tail knob which were at that time also attributed as a characteristic of S. tundra .…”
Section: Resultsmentioning
confidence: 94%